INTEGRATING COOPERATIVE LEARNING AND MUSIC: THE TALKING STICK STRATEGY TO IMPROVE SIMPLE PRESENT TENSE ACHIEVEMENT - Fibria Cahyani; Dyah Nugraheny Priastuti (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2025)
Grammar mastery, particularly the simple present tense, is crucial in developing students’ English proficiency. However, many junior high school students still face challenges in applying this tense accurately, leading to low achievement and reduced motivation in grammar lessons. Combining music and the Talking Stick creates a pedagogical synergy that targets the affective, social, and cognitive aspects of learning. This study aimed to examine the effect of integrating the Talking Stick technique with music on students’ achievement in the simple present tense. This research employed a quantitative quasi-experimental design with a one-group pre-test and post-test format. The sample of the study consisted of 12 seventh-grade students of SMP Taman Harapan Sidoarjo in the 2024/2025 academic year. Data were collected through simple present tense tests and analysed using the Wilcoxon test. This is evidenced by the increase in their average scores, from 60.3 in the pre-test to 74.7 in the post-test, indicating a meaningful academic gain. These findings demonstrated that combining the Talking Stick technique with music can effectively enhance students' achievement in the simple present tense, encourage active participation, and create a more engaging learning atmosphere. This approach can be a valuable alternative to traditional teaching methods, especially in junior high school.